Analisis Keabsahan Perjanjian Lisan Menurut Hukum Perdata di Indonesia - Deanna Fitri Roshandi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Agreements are an important instrument in everyday life, both in the social and economic spheres. In practice, agreements are not always made in written form, but are often made orally. This phenomenon raises legal questions about whether oral agreements have valid legal force and can be used as a basis for dispute resolution. This study aims to analyze the legal status of oral agreements from the perspective of Indonesian civil law by referring to Article 1320 of the Civil Code (KUHPerdata), which regulates the requirements for a valid agreement. The research method used is normative juridical with an approach to relevant laws and legal doctrines. The results of the study indicate that oral agreements remain legally valid as long as they meet the four requirements for a valid agreement: agreement of the parties, capacity to enter into an agreement, the existence of a specific object, and a lawful cause. However, the main problem arising from oral agreements is the difficulty in proving them when disputes arise, given the lack of written evidence that can be used as a basis before the law. Therefore, although civil law does not require a written form for the validity of an agreement, writing an agreement is still recommended to provide legal certainty, facilitate proof, and protect the interests of the parties. This finding underscores the importance of public legal awareness in choosing a form of agreement that is safer and has stronger evidentiary force.